2011
DOI: 10.1111/j.1474-9726.2011.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of age‐dependent changes in protein solubility identifies genes that modulate lifespan

Abstract: While it is generally recognized that misfolding of specific proteins can cause late-onset disease, the contribution of protein aggregation to the normal aging process is less well understood. To address this issue, a mass spectrometry-based proteomic analysis was performed to identify proteins that adopt sodium dodecyl sulfate (SDS)-insoluble conformations during aging in Caenorhabditis elegans. SDS-insoluble proteins extracted from young and aged C. elegans were chemically labeled by isobaric tagging for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
209
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(234 citation statements)
references
References 31 publications
21
209
3
1
Order By: Relevance
“…A number of studies have reported biophysical features, environmental conditions, and molecular partners that promote or repress the initial aggregation of specific proteins (1,3,7,(13)(14)(15). More recently, it has been recognized that the regulation of many other proteins is disrupted as a consequence of these initial aggregation events (8,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In a complementary approach, the origins of AD have been studied by analyzing Comparison between down-regulated and metastable biochemical pathways and networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported biophysical features, environmental conditions, and molecular partners that promote or repress the initial aggregation of specific proteins (1,3,7,(13)(14)(15). More recently, it has been recognized that the regulation of many other proteins is disrupted as a consequence of these initial aggregation events (8,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In a complementary approach, the origins of AD have been studied by analyzing Comparison between down-regulated and metastable biochemical pathways and networks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, protein aggregation is emerging as a widespread biological phenomenon, in which hundreds of different proteins can aggregate in aging, stress, or disease (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). To understand why some proteins aggregate whereas others remain soluble, we recently observed that many proteins in the proteome are insufficiently soluble relative to their expression levels (24).…”
mentioning
confidence: 99%
“…Protein aggregation is associated with many age-related disorders, and increased protein oxidation, mislocalization, and aggregation are observed in aged organisms [2][3][4][5][6][7]. Intuitively, these findings can be explained by a gradual decline in protein biosynthetic and quality control pathways and a progressive accumulation of protein damage.…”
mentioning
confidence: 92%
“…Despite this, why organisms age remains a complex mystery that if understood could have profound implications for the quality of human health. While the physiological decline associated with old age is easily recognizable, the mechanisms that determine aging are poorly understood; however, widescale loss of protein homeostasis (proteostasis) is proposed to be one of the "primary hallmarks of aging" [1].Protein aggregation is associated with many age-related disorders, and increased protein oxidation, mislocalization, and aggregation are observed in aged organisms [2][3][4][5][6][7]. Intuitively, these findings can be explained by a gradual decline in protein biosynthetic and quality control pathways and a progressive accumulation of protein damage.…”
mentioning
confidence: 99%
“…Notably, we and others have shown that several hundred proteins are highly prone to aggregate during normal aging in different model organisms. [15][16][17][18][19] In our recent study, 20 the proteomic analysis of the aggregating proteome from longlived C. elegans with reduced daf-2/insulin/IGF-1 receptor signaling highlighted a specific group of proteins namely RNA granule components. In particular we identified several stress granule components as well as 4 RBPs with LC prion-like domains thatbecamehighlyinsolublewithageincontrolanimals but not in long-lived animals.…”
Section: Introductionmentioning
confidence: 99%